Policy Effects of Ecological Red Lines on Industrial Upgrading and Health Promotion: Evidence From China Based on DID Model - Ye, Penghao (Frontiers in Public Health, 2022)
The implementation of the Ecological Red Lines (ERL) policy in China is under the background that natural resources have been immoderately exploited for serving rapid economic growth in the last 40 years, where the ecosystem's degradation happened and people's health could be affected. As the secondary industry is the contribution source of rapid growth as well as the threat source that threatens the natural environment and public health, the delimitation of ERL can act as a legal restriction that forces the industries to control the emissions and to upgrade the industrial composition. This paper conducts an ex-post policy evaluation on the improvement effects of industrial structure and residents' health and through ERL's pilot scheme in four provinces of China. By using the difference-in-differences (DID) method, the estimation results show that: (1) The industrial upgrading effect exists but to a small extent, as the ERL policy has generally elevated the tertiary industry's output by only 0.033% and hardly shown any promotion effects on the ratio of the tertiary industry to secondary industry; (2) The residents' health has been significantly improved by 1.029% after ERL policy on the whole, and enhanced over time mostly; (3) The health promotion effects are similar among three out of the four pilot provinces, whereas the industrial upgrading effects performed large heterogeneities among the four. These empirical results may provide references for the wider extension of ERL policy with more practical execution solutions in developing economies.